Effects of the interrelationship between dietary lysine and litter size on sow and litter performance - J L Laurin; R D Anderson; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1992)
One hundred and forty-three lactating primiparous sows were used in a study to determine the influence of four different litter sizes on the dietary lysine requirement as measured by sow and litter performance. At farrowing, sows were randomly assigned to one of three corn soybean meal diets (.67, .94, or 1.22 % lysine) and one of four litter sizes (8, 9, 10, or 11 pigs). Sows were fed 7.7, 9.9, and 12.1 IbId of their respective diet for the first, second, and third week of lactation. This provided an average daily lysine intake of 30.1, 42.2, or 54.8 gld throughout the 21-day lactation period. Ratio of other amino acids relative to lysine were kept constant to ensure that lysine was first limiting, and all diets contained 5% soybean oil to increase the energy density. Sows were fed twice daily, and feed disappearance was recorded each day. Litters were adjusted to their treatment size within 72 h after farrowing. If a pig died during the lactation period, a pig of similar age and weight was used as a replacement. Sows and litters were weighed weekly, and average backfat was measured at farrowing and weaning (d 21). There were no interactions between litter size and lysine intake for litter weight gain. Utter weight gain was increased by increasing litter size. Increasing dietary lysine tended to improve litter weight gain. A dietary lysine x litter size interaction was observed for sow weight loss. Sow weight loss was increased as litter size increased. However, increased dietary lysine reduced sow weight loss. Sow backfat loss was not affected by litter size or dietary lysine. In conclusion, it appears that sows require approximately 42.5 gld lysine to maximize 21-d litter weight gain. Surprisingly, litter size did not influence the sows lysine requirement. Increasing litter size increased sow weight loss, but this response was minimized by increasing dietary lysine.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Sows; Lysine; Reproductive performance; Litter size